1977
DOI: 10.1136/pgmj.53.621.356
|View full text |Cite
|
Sign up to set email alerts
|

The non-invasive recognition of left atrial enlargement: comparison of electro- and echocardiographic measurements

Abstract: SummaryThe aim of this study was to compare the ability of electro-and echocardiography to detect enlargement of the left atrium. Seventy-four patients, divided into three groups (eighteen normal, thirty-six valvular disease, twenty hypertension and/or coronary artery disease) were studied. The P wave terminal force in lead V1 (PTF-V1) was measured from a standard 12 lead electrocardiogram, and the internal left atrial dimension (LAD) was measured from time-motion echocardiograms. Linear regression analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In addition, the high specificity of the criteria of P wave axis < 30° to detect LAE has not been previously described to our knowledge. Compared with prior M-mode echocardiographic studies [ 16 , 18 , 23 , 25 ], we found higher sensitivity but lower specificity for P > 0.11s, and similar excellent specificity for P mitrale and NPTF-V1 > 0.04s·mm to detect CMR LAE. The overall increased sensitivity of ECG LAE compared to ECG RAE may be explained by a larger number of criteria used, as well as high prevalence of the very sensitive criteria P > 0.11s.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In addition, the high specificity of the criteria of P wave axis < 30° to detect LAE has not been previously described to our knowledge. Compared with prior M-mode echocardiographic studies [ 16 , 18 , 23 , 25 ], we found higher sensitivity but lower specificity for P > 0.11s, and similar excellent specificity for P mitrale and NPTF-V1 > 0.04s·mm to detect CMR LAE. The overall increased sensitivity of ECG LAE compared to ECG RAE may be explained by a larger number of criteria used, as well as high prevalence of the very sensitive criteria P > 0.11s.…”
Section: Discussionsupporting
confidence: 49%
“…An ECG in sinus rhythm, no more than 35 days from the CMR scan and prior to any pulmonary vein ablation procedures, was obtained for subjects with AF (n = 74). ECG LAE was defined by any one of the following: 1) P wave in any lead > 0.11s, 2) Notched P wave with interpeak duration > 0.04s (P mitrale), 3) P wave axis < 30°, 4) Area of negative P terminal force in lead V1 (NPTF-V1) > 0.04s·mm, or 5) Positive P terminal force in aVL (PPTF-aVL) > 0.5 mm [ 16 , 18 , 23 , 25 ]. ECG RAE included 1) P wave in inferior leads II, III, aVF > 2.5 mm or 2) Positive P wave in V1 > 1.5 mm [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, although there is an increased specificity of P wave duration from 20 up to 50 milliseconds, the possibility to discriminate the presence of LAE detected by echocardiography was poor. Similarly, in humans, individual ECG P wave changes (P wave duration, axis and morphology) do not reliably detect nor predict the presence of anatomic atrial enlargement, when compared with cardiac magnetic resonance imaging (Tsao and others 2008) or echocardiography (Ikram and others 1977; Lee and others 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them reported relatively low sensitivity but much higher specificity of these criteria, often approximating 100% [10,12] .…”
Section: Discussionmentioning
confidence: 99%
“…In the past, several studies have assessed the accuracy of ECG criteria in prediction of LA enlargement using echocardiography and often demonstrated conflicting results [10][11][12][13] . Most of them reported relatively low sensitivity but much higher specificity of these criteria, often approximating 100% [10,12] .…”
Section: Discussionmentioning
confidence: 99%